Integrated Advocacy Approaches In Refusing The Eviction Policy - Daneswara, Ramaditya Rahardian; S Kurnia, Nadya Audina (Jurnal Ilmiah Administrasi Publik, 2018)
This paper attempts to explore the approach of a policy advocacy pursued by residents of Central Jebres RT 02 and 03 RW 25, Jebres Village, Jebres Sub district, Surakarta City to reject the eviction policy carried out by the Surakarta City Government for the expansion of the Solo Techno Park (STP) land. A method in the study used descriptive qualitative namely the handling of their phenomena and give providing theoretical interpretation. The findings in the field indicate that the residents of Central Jebres conduct a series of policy advocacy, which among others, such as the formation of a core circle, choosing strategic issues, setting goals and strategies, processing data and packaging information, mobilizing supporters, influencing policy implementers, forming public opinion, creating a basis for movement and the latter monitor the work program. The results of the policy advocacy series conducted by the residents of Central Jebres who have joined the Jebres Demangan citizen alliance have not received positive results.